THU0002 Estrogen-Related Polymorphisms and Risk of Rheumatoid Arthritis: A Multicenter Study. (9th June 2015) - Canet, L.; Cáliz, R.; Lupiañez, C.B.; Canhão, H.; Filipescu, I.; Escudero, A.; Segura-Catena, J.; Soto-Pino, M.J.; Ferrer, M. Ά.; Pérez-Pampin, E.; González-Utrilla, A.; Lόpez-Nevot, M. Ά.; et al.
Abstract : Background: Rheumatoid Arthritis (RA) is a chronic autoimmune disease with higher prevalence and worse prognosis in women than men. Objectives: We aimed to determine whether 48 single nucleotide polymorphisms (SNPs) within steroid hormone signaling ( ESR1, ESR2, PGR, NR1I2, and SHBG ), phase I- and II-metabolizing enzyme ( HSD17B1, CYP1A1, CYP17A1, CYP1A2, CYP1B1, CYP2C9, CYP2C19, CYP3A4 and GSTP1 ) and hormone transporter ( ABCB1 ) genes influence on the risk of developing RA and whether genotyping of these variants might help to predict disease risk. Methods: The study population included 1357 RA patients and 1219 controls. Logistic regression analyses were performed to determine associations and to predict disease risk. Results: We found that carriers of the CYP2C19 rs4244285A allele and CYP3A4 rs11773597C/C genotype had a significantly increased risk of RA ( P =0.019 and P =0.0048) whereas carriers of the CYP2C9 rs1057910C and ESR2 rs4986938G alleles showed a reduced risk of developing the disease ( P =0.036 and P =0.0026). In addition, when a log-additive model was assumed, we observed a significant association for the CYP2C19 rs4244285, CYP3A4 rs2740574 and ESR2 rs4986938 SNPs suggesting an allele-dosage effect of these variants to modulate the risk of RA ( P =0.0076, P =0.044 and P =0.0004). Interestingly, a gender-stratified analysis also revealed that women carrying the CYP17A1 rs743572G/G genotype or the PGR rs518162A allele showed an increased risk of RA ( P =0.026 and P =0.032) whereas an opposite but not significant effect was observed in men ( P interaction =0.02 and 0.025, respectively). Furthermore, a rheumatoid factor (RF)-stratified analysis showed that seropositive patients carrying the SULT1A1 rs9282861A allele had a substantially increased risk of developing RA ( P =0.0088) whereas no effect was observed in seronegative patients ( P =0.56). Importantly, after correction for multiple testing ( P =0.0010), the association of the ESR2 rs4986938 SNP with a reduced risk of RA remained statistically significant ( P =0.0004) whereas the overall association of CYP2C19 rs4244285 and CYP3A4 rs2740574 or SULT1A1 rs9282861 in seropositive patients reached marginal significance ( P =0.0076, P =0.0048 and P =0.0088). Finally, a predictive analysis showed that a model including 3 genetic variants significantly associated with RA had a higher prediction capacity than a model including a similar number of non-significant SNPs (AUROC=0.562 vs. AUROC=0.513; -2log likehood ratio test P =4.24E-07). The predictive analysis showed that the ESR2 rs4986938 SNP had the highest predictive capacity ( P =0.00015), which along with a previous study demonstrating its correlation with ESR2 mRNA expression suggest a key role of this variant in the modulation of RA risk. Conclusions: These findings suggest that SNPs within estrogen-related genes may play a role in modulating susceptibility to RA and can be used to improve the prediction of disease risk. Disclosure of Interest: None declared